Peculiarities of neurocognitive and vegetative disorders and pain in patients in the acute phase of COVID-19 - Мудренко, Ірина; Kotkova, Олександра; Mudrenko, Віталій; Mamontov, Євген (Psychosomatic Medicine and General Practice, 2025)
Introduction. The COVID-19 pandemic has a negative impact on mental health, about 20% of patients who have suffered from COVID-19 have mental disorders. The most common manifestations are autonomic dysfunction, pain of various localization and intensity, and cognitive decline. The aim of the study was to identify the gender and age characteristics of the examined psychopathological features of pain, cognitive status, and autonomic dysfunction. Materials and methods. 66 patients during inpatient treatment in the acute phase of COVID-19 with radiologically confirmed lung damage were examined. Clinical, clinical-psychopathological, psychometric methods, and methods of mathematical statistics were used. The results. The presence of autonomic dysfunction syndrome is correlated with female gender (p≤0.001), age (p≤0.01), presence of depression (p≤0.001), anxiety (p≤0.001), presence of concomitant diseases (p≤0.001). The obtained data indicate greater vegetative reactivity in women, especially in the younger age group. In patients who were in the acute phase of COVID-19, cognitive impairment was detected according to MMSE results. In terms of gender, time orientation disorders were significantly more pronounced among female patients (p≤0.01); writing and reading (p≤0.1). The presence and deepening of cognitive function disorders in patients with covid 19 correlates with age (r=0.671), the presence of concomitant diseases (p≤0.001), and the presence of depression. Analysis of pain sensations using the Paindetect questionnaire confirmed the presence of neuropathic pain in 25.8% of respondents: 87.5% of women and 58.3% of men.Neuropathic pain in patients with Covid-19 is correlated with female gender, age over 50 years (p≤0.05), absence of a partner (p≤0.001), presence of depression (p≤0.01), anxiety (p≤0.001) and autonomic dysfunction syndrome (p≤0.001). At the same time, women mostly complained of headache, pain in the hands, pain in the neck and back; men were more concerned about pain in the legs, lower back and joints. At the same time, widespread localization of pain was more typical for men. The highest intensity of neuropathic pain was found in the age group of 46–60 years. Conclusions. COVID-19 negatively affects the autonomic nervous system, neurocognitive processes, and pain sensitivity. The frequency and intensity of these violations have gender and age characteristics. Vegetative dysfunction, pain in the acute phase of Covid-19 is comorbid with anxiety and depression. Keywords: COVID-19, pain, cognitive impairmant, autonomic dysfunction